PENGARUH SENAM IRAMA TERHADAP KEMAMPUAN MOTORIK KASAR ANAK USIA DINI DI TAMAN KANAK- KANAK AL HIDAYAH TABING KOTA PADANG - Dini Gusnita; Rakimahwati; Farida Mayar; Indra Yeni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the effect of rhythmic gymnastics on the gross motor skills of early childhood at Al Hidayah Tabing Kindergarten, Padang City. The study applied a quantitative approach with a pre-experimental method using a One Group Pretest-Posttest Design. The research subjects consisted of 20 children in group B aged 5–6 years. Data were collected through structured observation using an instrument in the form of a checklist containing seven indicators of gross motor skills. The test results showed that the instrument used had met the validity and reliability criteria. Treatment was given in the form of four implementations of Happy Movement Gymnastics. The analysis results showed that the average pre-test score of 13.25 (SD = 2.832) increased to 23.67 (SD = 2.535) in the post-test. The normality test using Shapiro-Wilk showed that the data were normally distributed, while the results of the paired sample t-test obtained a value of t = −17.857 with a significance value of 0.000 (<0.05). The findings show that H1 is accepted, so it can be concluded that rhythmic gymnastics has a significant influence on improving the gross motor skills of early childhood at Al Hidayah Tabing Kindergarten, Padang City.